2016
DOI: 10.1160/th15-09-0757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerobic exercise on haemostatic indices in paediatric patients with haemophilia

Abstract: C levels with exercise. The greatest improvement in haemostatic indices was observed in post-adolescent males with mild-moderate HA, who thus represent the group most likely to benefit from a reduction of bleeding risk in the setting of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…With the aim to validate these results, we have now repeated the study in a larger cohort consisting of 10 persons with severe HA and 10 matched controls. We have also examined whether the increased levels of VWF after physical exercise seen in our previous study, as well as described by others, might prolong the effect of factor concentrate administered just before exercise.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…With the aim to validate these results, we have now repeated the study in a larger cohort consisting of 10 persons with severe HA and 10 matched controls. We have also examined whether the increased levels of VWF after physical exercise seen in our previous study, as well as described by others, might prolong the effect of factor concentrate administered just before exercise.…”
Section: Introductionmentioning
confidence: 64%
“…Exercise has also been shown to increase levels of FVIII:C in healthy people as well as in patients with mild and moderate haemophilia A (HA). However, in patients with severe HA, no such increase has been shown …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Active children with hemophilia typically bleed less than their inactive/sedentary peers . With moderate to strenuous aerobic exercise, children with mild factor VIII deficiency can have a 2‐ to 2.5‐fold increase in baseline factor VIII levels …”
Section: Benefits Of Exercisementioning
confidence: 99%
“…25 With moderate to strenuous aerobic exercise, children with mild factor VIII deficiency can have a 2-to 2.5-fold increase in baseline factor VIII levels. 26,27 For patients with thrombosis, a systematic review of nine studies found that physical activity in adult patients with deep vein thrombosis (DVT) is overall beneficial. 28 Specifically, in the setting of an acute DVT, early exercise as compared with bed rest was associated with a more rapid resolution of limb pain and not associated with an increased risk of embolism.…”
Section: Benefits Of Exercisementioning
confidence: 99%